"A Review of Investment Choices Made by Salaried Employees" (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the investment preferences of salaried employees in Ettumanoor Municipality, Kerala, India. It aims to identify factors influencing their investment decisions, assess their knowledge and risk-taking capacity, and evaluate their levels of satisfaction. The study employs a questionnaire-based survey with 100 respondents.Key findings reveal a preference for bank deposits among respondents, driven primarily by savings motives. Most respondents exhibit moderate awareness of investment avenues and are comfortable with moderate risks. Factors influencing investment decisions include age, income, and family responsibilities. While satisfaction levels are generally high, respondents express concerns about potential risks and seek professional advice.The study suggests that promoting investment awareness, providing financial literacy training, and simplifying investment procedures can enhance employee investment behaviour and contribute to economic growth.